Encyclopedia of white-collar & corporate crime - Salinger, Lawrence M.; Gale Group (Thousand Oaks, Calif. Sage Publications, 2005)
Covers the history of white-collar and corporate crime. Serves as a general and non-technical resource for criminology and history students, librarians, and professors to understand the development of white-collar and corporate crime in the U. S. as well as internationally; to appreciate the business forces that can affect daily life; and to initiate educational discussion brought forth by the specific historical and topical articles presented in the work.
Electronic reproduction.
Keywords: White collar crimes -- Encyclopedias; Corporations -- Corrupt practices -- Encyclopedias; Commercial crimes -- Encyclopedias; Misconduct in office -- Encyclopedias; Political corruption -- Encyclopedias; Administrative agencies -- Corrupt practices -- Encyclopedias; Electronic books